Forensic Medical Findings in Child Sexual Violence: A Case Report - Septiawan, Dedi Andika; Arviandi, Rizki; Lubis, Adriansyah (Frontiers on Healthcare Research, 2024)
Background: Sexual violence is physical or psychological violence in sexual ways or by targeting sexuality. It includes sexual slavery, sexual torture, public sexual humiliation, sexual harassment, and rape. In Indonesia, the incidence of child sexual violence has increased. Based on KPAI data, 2019, there were 190 child victims of sexual violence. It increased to 419 victims in 2020. In North Sumatra Province, the PPPA Service states showed sexual violence is the most common type of violence with 609 cases of sexual violence against women and children. This case report aims to provide the role of forensic medical examination in case of sexual violence against a minor. Case report: In this case, the victim was a 14-year-old girl who admitted that she had been sexually violence by a person she had only met twice. The victim had bruises on the neck, chest, and breasts. She also had fresh lacerations on her hymen. The vaginal smear examination revealed spermatozoa were found. These findings were consistent with signs of sexual intercourse. Conclusion: The victim had suffered blunt force to the genitals that was consistent with signs of sexual intercourse as a sexual violence.